2019
DOI: 10.1101/745430
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bone-targeted lncRNA OGRU alleviates unloading-induced bone loss via miR-320-3p/Hoxa10 axis

Abstract: Although the underlying molecular mechanism of unloading-induced bone loss has been broadly elucidated, the pathophysiological role of long noncoding RNAs (lncRNAs) in this process is unknown. Here, we identified a novel lncRNA, OGRU, a 1816-nucleotide transcript with significantly decreased levels in bone specimens from hindlimb-unloaded mice and in MC3T3-E1 cells under clinorotation unloading conditions. OGRU overexpression promoted osteoblast activity and matrix mineralization under normal loading condition… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Studies have shown that Hoxa10 can participate in the research of regulating osteogenic differentiation. Increased expression can promote bone repair and osteogenic differentiation 25‐27 . Similarly, previous studies have confirmed that high‐fat diet can reduce the expression of Hoxa10 in mice and inhibit bone development 28 .…”
Section: Discussionmentioning
confidence: 74%
“…Studies have shown that Hoxa10 can participate in the research of regulating osteogenic differentiation. Increased expression can promote bone repair and osteogenic differentiation 25‐27 . Similarly, previous studies have confirmed that high‐fat diet can reduce the expression of Hoxa10 in mice and inhibit bone development 28 .…”
Section: Discussionmentioning
confidence: 74%